Arranjos de desenvolvimento da educação: uma alternativa partilhada de gestão municipal da educação - Nicoleti, João Ernesto [UNESP] (2014)
This study sought to investigate educational development as a form of organization between several municipalities with common educational issues and, together, they found differentiated forms of problem-solving and forward questions to government organizations, strengthening each other through actions of these regional educational arrangements. To do so, the Arrangement of Development of Education in Northwestern São Paulo State (ADENESP) was chosen as the object of analysis. This was an alternative that the municipalities in the region of Votuporanga found to organize a Regional Center of Educational Policies. The work is organized in three stages: the first refers to the consortiums between the country, states and municipalities in the most varied ways, showing that association between federated entities is not new; the second stage includes a study on the concurring opinion CNE/CEB nº 9/2011, which discusses arrangements for educational development, as well as other legal milestones for the function of said arrangements; the third step focuses on the experience of Arrangement of Development of Education in Northwestern São Paulo State, in forming and analyzing the actions taken by the arrangement from the study of his General Reports. In this analysis, the problems found by the municipalities, which are members of the arrangement, are presented as challenges for the municipal administration and are indicated in a diagnosis built from the Articulated Action Plan (PAR) of the Ministry of Education, constituting a kind of Regional PAR with the aim of guiding the work of the arrangement, in order that all municipalities can offer a quality education. The investigation concludes that the organization of municipalities with territorial proximity and common features in educational development arrangements can constitute itself as an alternative to the development of educational policies for the ...